Strengthening Self-regulated Learning in Teacher Education: An Analysis of Policy Alignment and Curriculum Integration - CP, Fathima Shajeena; Gafoor, K.Abdul (Voices of Teachers and Teacher Educators, 2026)
Equipping educators with strong Self-regulated Learning (SRL) skills empowers them to handle the demands of a rapidly changing society and educational reforms. SRL enables future educators to become lifelong learners and agents for nurturing SRL in their students, ultimately contributing to positive social transformation. In this context, this study critically analyses key policy documents including the National Education Policy 2020, the National Council for Teacher Education (NCTE) Amendment Regulations 2021, the NCTE Curriculum Framework for Integrated Teacher Education Programme (ITEP), and the Suggestive Syllabi for Secondary Stage ITEP. The research objective is to critically examine these documents’ explicit and latent references to enhance Self-regulated Learning (SRL) competencies among prospective secondary school teachers within the Integrated Teacher Education Programme (ITEP). The study utilizes a framework adapted from Zimmerman and Moylan’s (2009) Cyclical Model of SRL, by reviewing post-2005 experimental interventions on student-teacher selfregulated learning skills; encompassing five key components (Metacognition, Self-efficacy, Self-monitoring, Motivation, and Self-directed Learning) and seven core strategies (Taskanalysis, Reflective practices, Self-assessment, Collaborative learning, Feedback, Planning, and Problem-solving). NEP 2020 emphasizes integrating SRL strategies into teacher education programmes, fostering lifelong learners and reflective practitioners. The conceptual model adopted in the study confirms that the learners’ awareness of their thinking process, use of individualised learning strategies, and sustained motivation facilitate the development of teaching professionals who can handle the uncertainties of the rapidly changing society and related emerging reforms in higher education. The analysis reveals that while NCTE’s suggested syllabi explicitly incorporate SRL strategies within the course content, practicum, and assessment approaches during the four-year programme, only motivation receives substantial focus. This discordance calls for enhancing metacognitive awareness and cultivating positive self-efficacy beliefs among prospective teachers, empowering them to become lifelong learners and agents for imparting SRL in their professional practice. These observations of this study emphasize the importance of situated learning environments and a transformative teacher education approach to cultivate SRL abilities in teachers. Equipping educators with all important SRL skills that empower them to handle the demands of a rapidly changing society and educational reforms, aligns with national aspirations for social transformation.